2010
DOI: 10.1007/s11060-009-0106-z
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion weighted magnetic resonance imaging to distinguish the recurrence of metastatic brain tumors from radiation necrosis after stereotactic radiosurgery

Abstract: After stereotactic radiosurgery (SRS) for brain metastases, delayed radiation effects with mass effect may occur from several months to years later, when tumors may also recur. Aggressive salvage treatment would be beneficial for patients with recurrence, but may be contraindicated for those with dominant radiation effect. Conventional magnetic resonance (MR) imaging does not provide sufficient information to differentiate delayed radiation effects from tumor recurrence. Positron emission tomography, MR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(99 citation statements)
references
References 24 publications
2
97
0
Order By: Relevance
“…Nonstandard MRI sequences, including diffusion, perfusion-weighted and spectroscopy have been used to differentiate RN from PD. In particular, several reports have indicated that the relative cerebral blood volume (rCBV), derived from perfusionweighted sequences, can differentiate RN from PD with high accuracy [15,16]. In addition to MRI, radionuclide imaging with either single photon [17] or positron emitters [18][19][20] has also been tested in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Nonstandard MRI sequences, including diffusion, perfusion-weighted and spectroscopy have been used to differentiate RN from PD. In particular, several reports have indicated that the relative cerebral blood volume (rCBV), derived from perfusionweighted sequences, can differentiate RN from PD with high accuracy [15,16]. In addition to MRI, radionuclide imaging with either single photon [17] or positron emitters [18][19][20] has also been tested in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…For brain metastases, DSC-MR imaging yielded sensitivity and specificity values from 70% to 100% and 95.2% to 100% for differentiation of necrosis and tumor recurrence. 25,26 In differentiating tumor recurrence and radiation necrosis or pseudoprogression of primary gliomas, direct comparison between ASL and DSC-MR imaging showed no statistical significance, with sensitivity and specificity values of 79%-94% and 64%-88%. 20,27 In terms of detection of gliomas and metastases, ASL and DSC-MR imaging also showed similar diagnostic yields.…”
Section: Discussionmentioning
confidence: 99%
“…MRI diffusion-and perfusion-weighted imaging are the most rapid and accurate techniques (Mitsuya et al, 2010). However, for patients who are immobile and those with acute craniocerebral gunshot injuries, CEUS prove valuable in the absence of MRI or when rapid intervention is necessary.…”
Section: Discussionmentioning
confidence: 99%